2015
DOI: 10.1556/crc.2014.0034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple Insect-Pest Incidence on Yield in Basmati Rice

Abstract: The experiments for determining the multiple insect-pest incidence on yield loss in basmati rice was conducted for two crop seasons. Five treatments were, viz. application of imidacloprid in vegetative stage; application of granular insecticide in vegetative stage; application of higher dose of Urea; augmentive releases of yellow stem borer egg mass at vegetative and booting stage; untreated control. During both the years, the correlation between grain yield and dead heart, leaf folder damage and planthopper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
7
7
0
Order By: Relevance
“…The ranking of evaluation of ecofriendly insecticides under suppression over check (SPOC) against major insect pests of rice was observed as, Imidacloprid > CartapHcl > Neem Oil + Btk > Chlorantraniliprole > Indoxacarb > Chlorpyriphos > Thiamethoxam > Neem Oil > Btk for highest suppression over check; Imidacloprid > CartapHcl > Neem Oil + Btk > Chlorantraniliprole > Indoxacarb > Chlorpyriphos > Thiamethoxam > Neem Oil > Btk for lowest infestation of insect pests; CartapHcl > Imidacloprid > Neem Oil + Btk > Chlorantraniliprole > Indoxacarb > Chlorpyriphos > Neem Oil > Thiamethoxam > Btk for highest yield; and Imidacloprid > CartapHcl > Neem Oil + Btk > Chlorantraniliprole > Indoxacarb > Chlorpyriphos > Thiamethoxam > Neem Oil > Btk for mean of lowest infestation, highest suppression over check, and highest yield respectively (Table 3). Similar findings were reported by Chakraborty [9], Chakraborty and Deb [10], Kulagod et al [11], CRRI [21], Rath et al [12], Sarao et al [13] and Tigga et al [14].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The ranking of evaluation of ecofriendly insecticides under suppression over check (SPOC) against major insect pests of rice was observed as, Imidacloprid > CartapHcl > Neem Oil + Btk > Chlorantraniliprole > Indoxacarb > Chlorpyriphos > Thiamethoxam > Neem Oil > Btk for highest suppression over check; Imidacloprid > CartapHcl > Neem Oil + Btk > Chlorantraniliprole > Indoxacarb > Chlorpyriphos > Thiamethoxam > Neem Oil > Btk for lowest infestation of insect pests; CartapHcl > Imidacloprid > Neem Oil + Btk > Chlorantraniliprole > Indoxacarb > Chlorpyriphos > Neem Oil > Thiamethoxam > Btk for highest yield; and Imidacloprid > CartapHcl > Neem Oil + Btk > Chlorantraniliprole > Indoxacarb > Chlorpyriphos > Thiamethoxam > Neem Oil > Btk for mean of lowest infestation, highest suppression over check, and highest yield respectively (Table 3). Similar findings were reported by Chakraborty [9], Chakraborty and Deb [10], Kulagod et al [11], CRRI [21], Rath et al [12], Sarao et al [13] and Tigga et al [14].…”
Section: Resultssupporting
confidence: 88%
“…Rath et al [12] have been observed that, the infestations of yellow stemborer (Scirpophaga incertulus Walker) and rice earheadbug (Leptocorisa acuta Thunberg) were recorded lowest in Imidacloprid and highest grain yield was recorded in Thiamethoxam treated plots. Sarao et al [13] and Tigga et al [14] have been studied that, the infestation of yellow stemborer (Scirpophaga incertulus Walker) and rice earheadbug (Leptocorisa acuta Thunberg) were lowered by Imidacloprid.…”
Section: Introductionmentioning
confidence: 99%
“…(Table 3). Similar results were also reported by CRRI (2014) [3] , Rath et al (2014) [19] , Sarao et al (2015) [20] , Tigga et al (2018) [24] , and Sharanappa et al (2019) [21] . Present research work was adopted the lowest P:D ratio, respective to non-significant lowest infestation as scale to confined efficacy of insecticides as ecofriendly.…”
Section: Resultssupporting
confidence: 85%
“…Rath et al (2014) [19] have been reported that, plots treated with Imidacloprid recorded lowest infestation of rice earhead bug (Leptocorisa acuta) and highest grain yield followed by Thiamethoxam. Sarao et al (2015) [20] and Tigga et al (2018) [24] both have been found that, the damage rice earheadbug (Leptocorisa acuta) were recorded lowest in Imidacloprid. Sharanappa et al (2019) [21] have been found that, the application of Imidacloprid observed favour the high population of coccinellids.…”
Section: Introductionmentioning
confidence: 99%
“…Rath et al (2014) [23] has been reported that, plots treated with Imidacloprid recorded lowest infestation of yellow stemborer (Scirpophaga incertulus) and rice earhead bug (Leptocorisa acuta) and highest grain yield followed by Thiamethoxam. Sarao et al (2015) [25] and Tigga et al (2018) [30] both have been found that, the damage of yellow stemborer (Scirpophaga incertulus) and rice earhead bug (Leptocorisa acuta) were recorded lowest in Imidacloprid. Sharanappa et al (2019) [27] have been found that, the application of Imidacloprid observed favour the high population of coccinellids.…”
Section: Introductionmentioning
confidence: 99%